Decision making in orthopaedic trauma a theoretical, practical, and evidence-based text - Marmor, Meir T. (Thieme, 2017)
Decision Making in Orthopaedic Trauma is the largest compendium of orthopaedic trauma algorithms assembled to date. The decision trees cover a broad spectrum of cases - from simple isolated fractures - to severe, life-threatening conditions. Visually appealing, easy-to-comprehend decision trees detail underlying pathologies, suspected diagnoses, required imaging studies, possible treatment approaches, rehabilitation, expected outcomes, and postsurgical care. The format is more conducive to swiftly acquiring knowledge and making informed decisions than traditional texts and websites.